(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2015)
One of the most important reasons why beauty has been, is, and will possibly be exceedingly important for us is ethical at its core: by making us undergo the aesthetic experience of recognizing something ideal into something real, beauty can be the clearest symbol of our possibility, and even hope, of working on an ideal human measure, which means both the development of our identities as human beings and the development of more promising relationships between us, artifacts, and nature.